ROLE OF VITAMIN D IN CARDIOVASCULAR COMPLICATIONS OF METABOLIC-ASSOCIATED STEATOTIC LIVER DISEASE - Pivtorak, K.V.; Ivanchuk, O.V.; Pivtorak, N.A.; Burkov, M.V.; Pashinskyi, Y.M.; Shcherbeniuk, N.V. (World of Medicine and Biology, 2025)
Metabolic-associated steatotic liver disease is a systemic disease closely related to cardiovascular pathology. One of the key pathogenetic mechanisms of cardiovascular complications in such patients is endothelial dysfunction. It is manifested by impaired vascular tone, decreased production of vasodilators (in particular, nitric oxide), increased synthesis of adhesive molecules and activation of inflammatory cascades. This contributes to the development of atherosclerosis, arterial hypertension and impaired microcirculation. Vitamin D plays an important role in maintaining endothelial homeostasis. Its deficiency is often detected in patients with liver disease and is associated with more pronounced endothelial dysfunction. Vitamin D has anti-inflammatory properties, reduces the expression of pro-inflammatory cytokines and modulates the immune response, and also has a positive effect on insulin sensitivity. Thus, correction of vitamin D levels may be a promising direction in preventing vascular complications in patients with metabolic dysfunction-associated steatotic liver disease.
Keywords: metabolic-associated steatotic liver disease; endothelial dysfunction; vitamin D; nitric oxide; obesity; cardiovascular disease; diabetes mellitus